Mothers without their children - Beyer, Charlotte, 1965-; Robertson, Andrea, 1972- (Demeter Press, 2019)
Conceiving of and representing mothers without their children seems so paradoxical as to be almost impossible. How can we define a mother in the absence of her child? This compelling volume explores these and other questions from a range of interdisciplinary perspectives, examining experiences, representations, creative manifestations, and embodiments of mothers without their children. In her 1997 book, entitled Mother Without Child: Contemporary Fiction and the Crisis of Motherhood, the critic Elaine Tuttle Hansen urged for critical and feminist engagement with what she described as 'the borders of motherhood and the women who really live there, neither fully inside nor fully outside some recognizable "family unit", and often exiles from their children'. This book extends and expands this important enquiry, looking at maternal experience and mothering on the borders of motherhood in different historical and cultural contexts, thereby opening up the way in which we imagine and represent mothers without their children to reassessment and revision, and encouraging further dialogue about what it might mean to mother on the borders of motherhood."--